2003
DOI: 10.1081/mb-120021600
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of α and γ Phases in Isotactic Polypropylene with Low Ethylene Content: Isothermal Crystallization and Secondary Crystallization

Abstract: Crystallization and melting behaviors of isotactic polypropylene (IPP) with low ethylene content during an isothermal process and on heating just after it are investigated by means of in-situ x-ray diffraction. At every isothermal temperature investigated here, the formations of both and phases are confirmed. The ratio of to increases with an increase in isothermal temperature. On heating just after the isothermal process, the starts melting at lower temperature than the . This may be due to the small crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…This could be attributed to the nature of the m-iPP molecules and their dynamic behavior at 130 °C; this is in line with our previous research . It is interesting that, on cooling, X γ dramatically increases to 0.37, indicating that secondary crystallization facilitates the deposition of γ-crystal layers . On the basis of the SAXS data, the evolution of the lamellar structure is summarized in Figure c.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This could be attributed to the nature of the m-iPP molecules and their dynamic behavior at 130 °C; this is in line with our previous research . It is interesting that, on cooling, X γ dramatically increases to 0.37, indicating that secondary crystallization facilitates the deposition of γ-crystal layers . On the basis of the SAXS data, the evolution of the lamellar structure is summarized in Figure c.…”
Section: Resultssupporting
confidence: 88%
“…31 It is interesting that, on cooling, X γ dramatically increases to 0.37, indicating that secondary crystallization facilitates the deposition of γ-crystal layers. 32 On the basis of the SAXS data, the evolution of the lamellar structure is summarized in Figure 6c. As crystallization proceeds, the long spacing appears after 4 min during isothermal crystallization, changing from 28 to 14 nm (Figure 6d).…”
Section: ■ Resultsmentioning
confidence: 99%
“…The melting temperature increased with decreasing content of ethylene counits. 51 The other broader one located at lower temperature was due to the secondary crystallization 54 during cooling from isothermal crystallization temperature down to room temperature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It should be pointed out that the introduction of ethylene unit in iPP backbone can modify crystallization behavior of iPP, not only crystal morphology but also crystal structure. Early studies indicated that g-form crystals could be formed by short propylene sequences, while the long sequences crystallizaed into a-form crystals [19,24,[26][27][28][29][30][31][32][33]. Thus, the PPE may exhibit complicated crystallization behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Although investigation of the latter is not as wide as that of the former, recently, more and more attention has been drawn to the studies on the propylene-rich copolymers. Reports on thermal behavior [12][13][14][15], crystal structure [16][17][18][19], morphology [20][21][22][23], crystallization kinetics [13,14,[22][23][24][25] and polymorphism [19,24,[26][27][28][29][30][31][32][33] of propylene-ethylene copolymers (PPE) with minor ethylene contents have been published. However, the relationships between the chain structure and the crystalline morphology of the PPE have not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%